Conceptualizing and Investigating Instructor Presence in Online Learning Environments - Richardson, Jennifer C; Koehler, Adrie A.; Besser, Erin D.; Caskurlu, Secil; Lim, JiEun; Mueller, Chad M. (International Review of Research in Open and Distributed Learning, 2015)
As online learning opportunities continue to grow it is important to continually consider instructor practices. Using case study methodology this study conceptualizes instructor presence, the intersection of social and teaching presence as defined within the Community of Inquiry literature, and is based in the implementation phase of online courses which is important to note since instructors often teach courses they did not design or develop. The investigation of the instructor presence behaviors of 12 online instructors and the emerging profiles of instructor presence provide a gateway to strategies for online instructors and offer a window into the ways instructional presence elements work together while providing insights into how to make the best use of online instructor time. In practical terms, the profiling method provides a useful way for practitioners to improve their own experiences.